A protease-activated receptor-1 antagonist protects against podocyte injury in a mouse model of nephropathy - Yu Guan; Daisuke Nakano; Yifan Zhang; Lei Li; Wenhua Liu; Motohiro Nishida; Takashige Kuwabara; Asahiro Morishita; Hirofumi Hitomi; Kiyoshi Mori; Masashi Mukoyama; Tsutomu Masaki; et al. (Elsevier, 2017)
The kidney expresses protease-activated receptor-1 (PAR-1). PAR-1 is known as a thrombin receptor, but its role in kidney injury is not well understood. In this study, we examined the contribution of PAR-1 to kidney glomerular injury and the effects of its inhibition on development of nephropathy. Mice were divided into 3 groups: control, doxorubicinÂ +Â vehicle (15Â mg/kg doxorubicin and saline) and doxorubicinÂ +Â Q94 (doxorubicin at 15Â mg/kg and the PAR-1 antagonist Q94 at 5Â mg/kg/d) groups. Where indicated, doxorubicin was administered intravenously and PAR-1 antagonist or saline vehicle by subcutaneous osmotic mini-pump. PAR-1 expression was increased in glomeruli of mice treated with doxorubicin. Q94 treatment significantly suppressed the increased albuminuria in these nephropathic mice. Pathological analysis showed that Q94 treatment significantly attenuated periodic acidâSchiff and desmin staining, indicators of podocyte injury, and also decreased glomerular levels of podocin and nephrin. Furthermore, thrombin increased intracellular calcium levels in podocytes. This increase was suppressed by Q94 and Rox4560, a transient receptor potential cation channel (TRPC)3/6 antagonist. In addition, both Q94 and Rox4560 suppressed the doxorubicin-induced increase in activities of caspase-9 and caspase-3 in podocytes. These data suggested that PAR-1 contributes to development of podocyte and glomerular injury and that PAR-1 antagonists have therapeutic potential. Keywords: Protease-activated receptor-1, Podocyte, Transient receptor potential cation channel, Kidney injury